\(\frac{-2,6}{x}=\frac{-12}{42}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(-\frac{2,6}{x}=-\frac{12}{42}\)
\(-2,6\cdot42=-12\cdot x\)
\(\frac{109,2}{12}=x\Rightarrow x=9,1\)
a)\(\) Ta có : x / 3,15 = 0,15 / 7,2
(=) x = 0,15 . 3,15 / 7,2
= 21 / 320
b) Ta có : -2,6 / x = -12 / 42
(=) x = -2,6 . 42 / -12
= 91 / 10
\(a.\) \(\frac{x}{3.15}\) \(=\) \(\frac{0.15}{7.2}\)
<=> \(x=\) \(\frac{0.15\cdot3.15}{7.2}\)
<=>\(x=0.065625\)
\(b.\) \(\frac{-2.6}{x-11}=\frac{-12}{42}\)
<=>\(x-11=\frac{-2.6\cdot-12}{42}\)
<=>\(x-11=0.742857142\)
<=>\(x=11.74285714\)
\(3\frac{4}{5}:2x=0,25:2\frac{2}{3}\)
\(\Leftrightarrow\frac{19}{5}:2x=0,25:\frac{8}{3}\)
\(\Leftrightarrow\frac{19}{5}:2x=0,25\cdot\frac{3}{8}\)
\(\Leftrightarrow\frac{19}{5}:2x=\frac{3}{32}\)
\(\Leftrightarrow2x=\frac{19}{5}:\frac{3}{32}=\frac{19}{5}\cdot\frac{32}{3}=\frac{608}{15}\)
\(\Leftrightarrow x=\frac{608}{15}:2=\frac{608}{30}=\frac{304}{15}\)
\(\frac{-2,6}{12}=\frac{x}{-42}\Leftrightarrow x=\frac{\left(-2,6\right)\left(-42\right)}{12}=9,1\)
\(\frac{1,4}{-5}=\frac{2,1}{x}\Leftrightarrow x=\frac{2,1.\left(-5\right)}{1,4}=-7,5\)
\(\frac{3}{x-1}=\frac{21}{16}\Leftrightarrow x-1=\frac{3.16}{21}=\frac{16}{7};x=\frac{23}{7}\)
\(\frac{1,2}{30}=\frac{3x+4}{50}\Leftrightarrow3x+4=\frac{50.1,2}{30}=2;3x=-1;x=-\frac{1}{3}\)
a) \(\frac{-2,6}{12}=\frac{x}{42}\)
\(x=\frac{-2,6.\left(-42\right)}{12}=9,1\)
b) \(\frac{1.4}{-5}=\frac{2,1}{x}\)
\(x=\frac{-5.2,1}{1,4}=-7,5\)
c) \(\frac{3}{x-1}=\frac{21}{16}\)
\(x-1=\frac{3.16}{21}=\frac{16}{7}\)
\(x=\frac{16}{7}+1=\frac{23}{7}\)
d) \(\frac{1,2}{30}=\frac{3x+4}{50}\)
\(3x+4=\frac{12.50}{30}=20\)
\(3x=20-4=16\)
\(x=16:3=\frac{16}{3}\)
\(a,\frac{-2,6}{x}=-\frac{12}{42}\)
\(\Leftrightarrow\left(-2,6\right).42=-12x\)
\(\Leftrightarrow-12x=-\frac{546}{5}\)
\(\Leftrightarrow x=\frac{91}{10}\)
\(b,\frac{x^2}{6}=\frac{24}{25}\)
\(\Leftrightarrow25x^2=24.6\)
\(\Leftrightarrow25x^2=144\)
\(\Leftrightarrow x^2=\frac{144}{25}\)
\(\Leftrightarrow x=\frac{12}{5}\)
Ta có: \(\frac{x-2}{12}+\frac{x-2}{20}+\frac{x-2}{30}+\frac{x-2}{42}=42^5:\left(2^3\cdot21^6\right)\)
\(\Leftrightarrow\left(x-2\right)\left(\frac{1}{12}+\frac{1}{20}+\frac{1}{30}+\frac{1}{42}\right)=\frac{2^5\cdot21^5}{2^3\cdot21^5\cdot21}\)
\(\Leftrightarrow\left(x-2\right)\cdot\frac{4}{21}=\frac{4}{21}\)
\(\Leftrightarrow x-2=1\)
hay x=3
Vậy: x=3
\(x\left(\frac{1}{6}+\frac{1}{12}+\frac{1}{20}+\frac{1}{30}+\frac{1}{42}+\frac{1}{56}+\frac{1}{72}+\frac{1}{90}\right)=\frac{4034}{5}\)
\(x.\frac{2}{5}=\frac{4034}{5}\)
\(x=\frac{4034}{5}:\frac{2}{5}\)
\(x=\frac{4034}{5}.\frac{5}{2}\)
x = 2017
\(\frac{-2,6}{x}=\frac{-12}{42}\Rightarrow x=-2,6:\frac{-12}{42}=\frac{13}{5}:\frac{2}{7}=\frac{91}{10}=9,1\)
Ta có: \(\frac{-2,6}{x}=\frac{-12}{42}\)
\(\Rightarrow x=42.\left(-2,6\right):\left(-12\right)\)
\(\Rightarrow x=9,1\)
Vậy x = 9,1